Nanostructured Mg and Al oxides by a combustion synthesis method and fabrication of the thin films by pulsed laser deposition / Nurhanna Batar@Badar - Batar@Badar, Nurhanna (Institute of Graduate Studies, UiTM, 2015)
In this research, the novel properties and potential applications of some nanostructured metal oxides and thin film metal oxides were studied. This work consists of mainly two parts, firstly the nano and micron powders investigation and secondly the thin film characteristics. The characteristics of nano powders have to be investigated first before thin film nanostructures are being researched, that is why it is important to study the characteristics of Al₂O₃ and MgO nano powders first. MgO and Al₂O₃ nano powders and its doped materials, Mg1₋ₓCuₓO (x = 0.02, 0.04, 0.06) and Al₂₋ₓCrₓO₃(x = 0.1, 0.2, 0.3) were synthesized using a combustion method. The study on doped compounds is to investigate band gap changes in the new materials. The synthesis conditions were optimized to obtain pure nanostructured metal oxides. In this work, it is found that the synthesis route using triethanolamine for the combustion synthesis is suitable in obtaining pure and single phase MgO, Al₂O₃, Mg1₋ₓCuₓO and Al₂₋ₓCrₓO₃materials. The presence of substitutional elements in the MgO and Al₂O₃ lattice had caused changes in morphologies and crystallite size of the materials…